Sub Contractors in Government Procurement Contract of Goods and Services - Merry Tjoanda (University of Udayana, 2022)
This research aimed to review and analyze the position of sub contractors in government procurement contract of goods/services and how the legal relationship between sub contractors and contractors in government procurement contract of goods/services. The research method used normative juridical. The approach used are the statute approach and the conceptual approach. From the results of this research it was concluded that; (1) Subcontractors as subjects of contract law are regulated in various laws and regulations, especially those government procurement contract of goods/services. This subcontractors have legal standing in contractual relationships, especially in government procurement contracts of goods/services. (2) The subcontractor has a legal relationship with the Contractor as a service provider based on the subcontract but has no legal relationship with Commitment-Making Officer (CMO)/PPK as a service user.